Enhancing Solubility of Recombinant Plasmodium Lactate Dehydrogenase (pLDH) Using Combination of Cold-Inducible Expression System and Cold-Stirred Bioreactor - Alimuddin; Muhamad Ali; Sahrul Alim; Muhamad Amin (Bogor Agricultural University, Indonesia, 2023)
A major drawback associated with an expression of a high-level Plasmodium Lactate Dehydrogenase (pLDH) using Escherichia coli is the low solubility due to the formation of an inclusion body (IB). This study aimed to develop a suitable protocol for enhancing the solubility of pLDH expressed in E. coli. Firstly, a pLDH-encoding gene was amplified from the blood sample of malaria-infected patients and ligated into pBlueScript II KS+ for sequencing. Afterward, the pLDH gene was digested and cloned into pColdTF for expression. The recombinant plasmid was transformed into the E. coli BL21 (DE3) RIPL Codon Plus Strain. Then, the bacterial host was initially cultured at 37°C until reaching optical density (OD) at 600 nm: 0.5. Thereafter, the growth temperature was lowered to 15°C, followed by the addition of 0.1 mM IPTG into the culture medium for inducing pLDH expression. Thereafter, the bacterial hosts were cultured in a cold-stirred bioreactor (15°C). The result showed that a combination of the low culture conditions (15°C) and a low amount of IPTG increased the solubility of pLDH. This result suggests that this protocol can be a convenient method for generating high-quality recombinant protein using the E. coli system.